2018
DOI: 10.3389/fonc.2018.00347
|View full text |Cite
|
Sign up to set email alerts
|

Sphere-Formation Assay: Three-Dimensional in vitro Culturing of Prostate Cancer Stem/Progenitor Sphere-Forming Cells

Abstract: Cancer Stem Cells (CSCs) are a sub-population of cells, identified in most tumors, responsible for the initiation, recurrence, metastatic potential, and resistance of different malignancies. In prostate cancer (PCa), CSCs were identified and thought to be responsible for the generation of the lethal subtype, commonly known as Castration-Resistant Prostate Cancer (CRPC). In vitro models to investigate the properties of CSCs in PCa are highly required. Sphere-formation assay is an in vitro method commonly used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 62 publications
2
159
0
Order By: Relevance
“…Therefore, recent efforts are being directed towards targeting CSCs . We evaluated the ability of ST1926 to target this sub‐population of stem/progenitor cells, in DU145 and PC3 cells, using a 3D sphere formation assay . Interestingly, a recent study elucidated the role of retinoic acid, one of the products of ALDH isozymes, and other vitamin A derivatives such as ATRA, in suppressing ALDH activity among CSCs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, recent efforts are being directed towards targeting CSCs . We evaluated the ability of ST1926 to target this sub‐population of stem/progenitor cells, in DU145 and PC3 cells, using a 3D sphere formation assay . Interestingly, a recent study elucidated the role of retinoic acid, one of the products of ALDH isozymes, and other vitamin A derivatives such as ATRA, in suppressing ALDH activity among CSCs .…”
Section: Discussionmentioning
confidence: 99%
“…53 We evaluated the ability of ST1926 to target this sub-population of stem/progenitor cells, in DU145 and PC3 cells, using a 3D sphere formation assay. 4,[28][29][30] Interestingly, a recent study elucidated the role of retinoic acid, one of the products of ALDH isozymes, and other vitamin A derivatives such as ATRA, in suppressing ALDH activity among CSCs. 54 We showed that treatment with ST1926 at a concentration as low as 0.01 µmol/L inhibited drastically the SFU as well as the sphere size over five generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sphere formation assay was used as previously reported by our lab [19, 20]. In brief, single SH-SY5Y and SK-N-SH cell suspensions (10×10 3 cells/well) were seeded in Matrigel™/serum free DMEM Ham’s F-12 (1:1).…”
Section: Methodsmentioning
confidence: 99%